Acute Respiratory Failure as the First Manifestation of Antisynthetase Syndrome - Toujani, Sonia (Tanaffos, 2017)
We report the case of a 40-year-old man with acute respiratory failure syndrome that later proved to be an initial manifestation of antisynthetase syndrome. The diagnosis of this rare combination of a connective tissue disease and an acute respiratory failure is difficult in a previously asymptomatic patient. Early diagnosis and immunosuppressive therapy started precociously prevented the disease progression and resulted in a good outcome.